Jewish culture and history as an inspiration to design Jewish museums: a case study of Jewish Museum Berlin - Alosaimi, Faisal (2019)
This research investigates the effect of Jewish history and culture as an inspiration to conceptualise the architecture of Jewish museums in order to connect the visitors intellectually and/ or emotionally with spatially enhanced and evocative spaces. Since there are now sixty-nine Jewish museums devoted to Jewish history, a rational model has been applied to select the most appropriate case study for detailed consideration. Using this model resulted in identifying the Jewish Museum in Berlin (JMB), Germany, as the focus of this research. The examination of this study delves into two issues: first, how the Jewish history and culture can affect the design of the JMB; second, how the general public will interpret the meanings of its museum architecture. Based mainly in ‘a cognitive theory of religious transmission’, the research develops a conceptual framework of ‘divergent modes of meaningful transmission experiences’ as an approach to examine the effect of Jewish history and culture in designing and interpreting the museum architecture of the JMB. This research is a combination of conceptual and empirical research. In terms of the conceptual part, the theoretical framework for analysing the visitor’s experience in the JMB has been arranged in a hierarchical structure consisting of two main layers. The first layer is based on two modes of transmission of religious knowledge in Harvey Whitehouse’s philosophy – doctrinal and imagistic. The second layer containing two separate theories: kabbalah as interpretive method and epic theatre. Also, as part of the conceptual research, a wide review of the literature draws on various key aspects such as interpretive museum, performing the museum and architecture. As far as the empirical research is concerned, the case study method is the main approach to examine the phenomenon of this research within its real life context by collecting and analysing different sources of evidence (interviews, direct observation, responses from the museum’s visitors from different platforms, and formal analysis). Two categories of experience have been identified in JMB (cognitive and embodied experience) demonstrating the effect of Jewish history and culture on conceptualising the museum architecture. Based on the analysis of the visitor’s interpretation, it is apparent that the embodied experience has more psychological impact on the visitor than the impact of the cognitive experience. In contrast, the cognitive experience has more socio-political impact on the visitor than the impact of the embodied experience. However, the combination of these two modes in one museum can help to create a spatial environment that each mode of the two most likely will overcome the limitation of the other mode. This combination seems to work well in the basement level, whereas it does not work appropriately in the permanent exhibition of the JMB.